ABOUT ADDENDA TO CALCULATION METHOD OF THE ORBITS EAS ON POSITION AND VELOCITIES - Paltsev, N. G. (Одеські астрономічні публікації, 2017)
On base of the analysis of the motion EAS and algorithm of the calculation of their orbits and ephemerides motion EAS in space is presented by amount two main motions: motion EAS in planes of the orbit and motion to planes of the orbit. Such presentation of the motion EAS most corresponds to the classical calculation method of their orbits on position and velocities. Whereas, measured velocity EAS garbled indignations of the node, slopping and average anomaly, to method once-is worked addition, allowing take into account the influence of these indignations on motion EAS and, hereunder, more correct to calculate the elements of their orbits. Cite an instance calculation of the orbits certain-torah EAS and comparisons result calculations, confirming a finding made by author.